Efficacy of Multimodal Analgesic Injections in Operatively Treated Ankle Fractures: A Randomized Controlled Trial. (18th December 2019) - Hancock, Kyle John; Rice, Olivia M.; Anthony, Chris A.; Glass, Natalie; Hogue, Matthew; Karam, Matthew; Marsh, J. Lawrence; Willey, Michael C.
Abstract : Background: Pain management following surgical treatment of an ankle fracture is an under-studied area of clinical practice. The present study evaluated the efficacy of a multimodal surgical-site injection as an adjunct to postoperative pain management in patients with an operatively treated, closed, rotational ankle fracture. Methods: Patients indicated for operative fixation of a rotational ankle fracture were randomized to receive multimodal surgical-site injection (ropivacaine 200 mg, epinephrine 0.6 mg, and morphine 5 mg) or no injection (control). Visual analog scale (VAS) pain and opioid consumption data were collected every 4 hours until discharge from the hospital. Length of stay and discharge destination were recorded. Patients were sent automated text messages to report VAS pain and opioid usage during the first 2 weeks after discharge. Results: One hundred patients (49 injection and 51 control) were enrolled. Demographic data were similar between the 2 groups. Mean VAS scores over the first 24 and 48 hours postoperatively were slightly lower in the injection group (42 ± 3 and 41 ± 3, respectively) compared with the control group (52 ± 3 and 50 ± 3, respectively; p = 0.01 and p < 0.01, respectively). The median opioid usage, in terms of morphine equivalent dose, was similar over the first 24 hours between the injection group (25.5; range, 0 to 74.7) and the control group (28.3; range, 2.5 to 91.0; p = 0.35). The median opioid usage from recovery room admission to discharge was also similar between the injection group (29.0; range, 0 to 85.3) and the control group (32.7; range, 4.3 to 215.0; p = 0.35). There were no differences in outpatient VAS scores or opioid consumption during the first 2 weeks postoperatively as assessed with use of automated text messaging. Median length of stay was 22.3 hours (range, 1.7 to 182.3 hours) for the injection group and 22.5 hours (range, 2.2 to 123.3 hours) for the control group (p = 0.71). The response rate for the post-discharge automated text messages was 85.1%. Complication rates were similar. Conclusions: The use of multimodal surgical-site injections in operatively treated rotational ankle fractures is associated with a reduction in immediate in-hospital pain scores that is statistically significant but below the minimal clinically important difference. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.